(3Uhf GdefWb hGdcdGe Yf af GdefWb hGdcdGes - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3GdMeO ddg hSdGe Ydi YHGOg GdPjf GUWai SejJg Gdbhd GdeTQb dRe efg GdEfLQGQ Edi fbd fUhU GdCFeg ai efg GdfXQ ai Yde GdcdGe s
(3BNQgG (B:s
(3gPG BNQ eG dNUJg ef cJGH GHf Jjejg ChQOJ YHGQJg HdaXg ef ZjQ JUQa ai GdZGdH hddg GdMeO hGdefI s
(3GdfSNI HgG MhGTs
(3aQZ efgG eDdagG SfI (B888s
(3YdjgG Jedc SfI (B1014 s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B128 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B534s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds